Caracterização da atividade física, composição corporal e força muscular da população rural e urbana - Paula Júnior, Célio Antônio de (2017)
Population aging is a reality in Brazil, and this process can lead to increased incidence of chronic-degenerative illnesses as well as frailty syndrome and sarcopenia. Also, a general health condition is established, in which muscle strength is insufficient to carry out routine activities associated with an independent lifestyle. The situation is aggravated by the sedentary lifestyle of the population, as the clinical conditions derived from the lack of physical activity are directly responsible for the mortality of millions of people per year. In Brazil, studies on the health of the population are still very much attached to urban population, and the rural reality remains limited regarding epidemiological research. In the light of the above, this study has the objective of analyzing the body composition, level and volume of physical activity and muscle strength in urban (n=55), rural industrial (n=45) and rural family agriculture (n=44) residents. A cross-sectional study is presented herein. The study volunteers were initially approached at basic health units and therefore the proportion of individuals diagnosed with non-transmissible chronic diseases within the study sample is significant for the three realities studied. Tetrapolar bioimpedance was utilized to assess body composition, handgrip strength and dorsal dynamometer were used to measure muscle strength, and triaxial accelerometer was utilized by the volunteers during seven consecutive days. Descriptive statistical methods were utilized to characterize the population, and Kolmogorov-Smirnov and Shapiro-Wilk were applied to verify data normality. ANOVA and Kruskall Wallis were applied to repetitive measurements with post hoc Bonferroni and Dunn, respectively, to evaluate the differences between locations (urban, rural agricultural, and rural industrial). Binary logistic regression, with the forward method, was utilized to verify the relationship between the level of physical activity (independent variable) and location (dependent variable), adjusted by age, Body Mass Index (BMI), sex, and muscle strength. Spearman's coefficient was employed to verify the correlation between BMI and the Metabolic Equivalent (MET), daily caloric expenditure (kcal), and the number of steps taken, during one week, according to the location. An acceptable statistical significance level was established as p<0.05. The results of this study indicate that the level of physical activity is significantly lower and differs in volume and intensity patterns for urban subjects (p<0.001) in comparison with rural realities (p<0.001), both for rural agricultural families and those in rural industrial settings. Rural volunteers were more active overall, and presented higher levels of Moderate and Vigorous Physical Activity (MVPA) practice. Sedentary lifestyle, identified by the light activity pattern and time spent sitting, was a behavior more associated with urban population (9.05±1.72 sitting hours), resulting in higher accumulation of fat (35.55±7.9% fat) and BMI (27.3±4.7 kg/m2). This scenario represents additional risk for the development of non-transmissible chronic diseases, besides reducing the quality of the skeletal muscle and muscle strength. When related to family agriculture, urban, and rural industrial settings, statistically significant relationships were established for all levels of physical activity: light, p<0.001; moderate, p<0.001; vigorous, p<0.001; very vigorous, p=0.001; MVPA, p<0.001. Regarding the number of steps, it was observed that the fourth day for the rural family group was the most intense, with an average of 12.245.1±3.603.7 steps and significance p<0.001. For the urban volunteers, Sundays presented the lowest average, with 4.672.3±1420.3 steps and significance p<0.001. Overall, the rural family settings registered the highest averages of steps across all weekdays and weekends, while urban settings were responsible for the lowest values recorded during the study. It was concluded that the level of physical activity is significantly lower and differs in volume and intensity patterns for urban subjects in comparison with rural settings (family agriculture and rural industrial), which were more active and presented higher levels of MVPA. Sedentary lifestyle, identified by light activity patterns and time spent sitting, was more associated with urban populations, resulting in higher accumulation of fat and higher BMI, representing additional risks for the development of non-transmissible diseases, besides reducing the quality of the skeletal muscle and muscle strength.